Asuhan Keperawatan Keluarga dengan Masalah Merokok dan Kebiasaan Mengonsumsi Makanan Cepat Saji pada Remaja (IJM: Journal of Multidisiplinary, 2025)
Adolescents are particularly vulnerable to engaging in high-risk health behaviors, such as smoking and the frequent consumption of fast food. These behaviors are often shaped by environmental influences, lifestyle patterns, and limited health literacy. They are strongly associated with increased risks of obesity, cardiovascular disease, respiratory disorders, and a diminished overall quality of life. This study employed a case study approach in the context of nursing care, encompassing assessment, diagnosis formulation, care planning, implementation, and evaluation. This study aimed to describe a family-centered nursing care for adolescents exhibiting smoking behavior and unhealthy dietary patterns. Nursing interventions were structured around the five key family health tasks. For smoking-related issues, interventions included health education on the dangers of smoking, application of the Spiritual Emotional Freedom Technique (SEFT), and environmental modifications within the home to promote a smoke-free lifestyle. For dietary concerns, interventions comprised nutrition education, encouragement of healthy snack choices, the use of the "My Plate" visual aid through interactive puzzle-based media, behavioral modification techniques, and referrals to nearby healthcare facilities for further support. Post-intervention evaluations indicated notable improvements in the family’s knowledge, skills, and motivation in supporting adolescent health. These changes contributed positively to the adolescent’s health behaviors and overall well-being.